A study on postponed purchase behaviour in Singapore - Lim, Jeanne Gek Bee (2008)
In a retail climate where there is stiff competition amongst retailers and numerous sales, customers may tend to postpone their purchase during non-sales periods and wait for sales. Our descriptive research on Singaporean consumers shows they have an inclination towards displaying postponed purchasing behaviour. We also investigated the demographics and attitude of consumers who displayed postponed purchase behaviour towards sales.